Avaliação do ITS1 e do ITS2 como barcode para Calanoida (Crustacea, Copepoda) marinhos e como marcador complementar para filogenia do grupo - Rocha, Gustavo Martins (2014)
Calanoida is the most abundant copepod Order in the world, having recognized ecological and scientific importance. But the accurate morphological taxonomic identification of this animal group is not simple, requiring years of experience and practice, especially when working with specimens in larval and juvenile stages. Thereat, molecular identification through DNA barcode is an important tool for assistance the identification of these organisms on the species taxonomic level. The mitochondrial marker Cytocromo Oxydase I (COI) is considered standard for molecular identification of most animal groups, but it doesn’t seems as efficient for calanoid copepods. This study aimed to test the two subunits of the nuclear molecular marker Internal Transcribed Spacer (ITS1 and ITS2) as a barcode for this animal group. We tried to sequence ITS1, ITS2 and COI from 105 individuals representing 14 families of Calanoida. Sequencing success rates of nuclear markers were much higher than those from COI (98%, 91% and 34%, respectively). In addition, it was found a gap between intraspecific and interspecific genetic distances for the nuclear molecular markers that allow grouping 100% of the sampled individual’s sequences with other individuals’ from the same species in monophyletic clades for ITS2 and with one exception for ITS1. Phylogeny of Calanoida, based on ITS1-ITS2-COI concatenated sequences, proved to be congruent with what has already been established in relation to the evolutionary relationships of species in the group. Despite the need for additional studies to confirm the patterns found here, we can conclude, based in our results, that both ITS1 and ITS2 are molecular markers that are easy sequenced and have enough variation to be used for DNA barcoding of marine calanoids.